Drying kinetics, thermal and morphological analysis of starchy food material: Experimental investigation through an induced type solar dryer - Sengar, Mukul; Singhania, Reeta Rani; Singh, Deepak; Mishra, Pradeep Kumar; Singh, Dhananjay; Kumar, Manish; Giri, Balendu Shekher (Elsevier B.V., 2023)
Solar drying is a green and clean energy-based technique for food preservation. In this study, drying kinetics and thermal, and morphological analyses of food material have been investigated. A mathematical model has also been studied and modified to validate experimental findings. An induced-type solar dryer setup has been fabricated and experiments have been conducted with potatoes as food samples. The weight loss and temperature variations were monitored in all three types of food samples. The average drying efficiency of the dryer has been found as 20.3 %. Scanning electron microscopy analysis has also been done to examine the surface morphology of the solar-dried food samples. The spherical-shaped sample has shown interesting results and they have the quality to attain maximum temperature due to the small surface area among all three shapes. The fabricated experimental setup has an initial cost and better payback period of $ 205.78 and 1.50 yr respectively.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: Drying characteristics; Economic analysis; MATLAB; Potato; Solar dryer; Drying; Food preservation